The Dilemma of Public Service Innovation in Enhancing Public Value - Agusniar Rizka Luthfia; Eka Nada Shofa Alkhajar (International Journal of Social Science and Humanity, 2025)
Public service innovation across various levels of government represents a positive sign of progress in Indonesia’s bureaucratic reform efforts. In practice, however, it is essential to ensure that such innovations genuinely enhance the public value of existing services so that they effectively address the needs of service recipients. Field evidence indicates that the implementation of public service innovations continues to face multiple challenges. The public value generated by an innovation may vary—or even fail—when viewed from the perspectives of different stakeholder groups. This study examines these dilemmas, an area that remains relatively underexplored. Employing a qualitative approach that includes in-depth interviews, observation, and a review of relevant literature, the research finds that failures in public value often arise from inherent dilemmas within public service innovation itself. Accordingly, government administrators are expected to develop a clear understanding of the values that should be embedded in the public service innovations they implement. Furthermore, attention must be paid to variations in social conditions and local cultures, as enhancing public value requires alignment between the values underpinning innovation and the cultural context of the community it serves. Finally, public sector organizations, as the primary agents of practical implementation, must provide legitimate mechanisms to reconcile value conflicts when they arise.